2014
DOI: 10.1007/s13205-014-0198-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic diversity of polyhydroxybutyrate (PHB) producing Pseudomonas putida isolates of Chhattisgarh region and assessment of its phosphate solubilizing ability

Abstract: A diverse and versatile spectrum of metabolic activities among isolates of fluorescent Pseudomonas putida indicates their adaptability to various niches. These polyhydroxybutyrate producing and phosphate solubilizing isolates showed a high level of functional and genetic versatility among themselves. One of the potential P. putida isolate P132 can contribute as a candidate agent for both biocontrol and PGPR applications. Identified as one of the most efficient PHB producer and phosphate solubilizer, in vitro d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…The metabolism of bacteria possessing high polyhydroxybutyrate (PHB) production capabilities, for whose generation acetyl-CoA and acetoacetyl-CoA are early precursors, therefore provides a more suitable starting point for optimization toward isoprenoid production via the MVA pathway. Such microorganisms are, for example, the bacteria Pseudomonas putida, Cupriavidus necator, or Methylobacterium extorquens, in which acetoacetyl-CoA is furthermore an essential intermediate of the anabolic metabolism. As a proof-of-concept, introducing the MVA pathway in M.…”
Section: Metabolic Engineering Toward Industrial Productionmentioning
confidence: 99%
“…The metabolism of bacteria possessing high polyhydroxybutyrate (PHB) production capabilities, for whose generation acetyl-CoA and acetoacetyl-CoA are early precursors, therefore provides a more suitable starting point for optimization toward isoprenoid production via the MVA pathway. Such microorganisms are, for example, the bacteria Pseudomonas putida, Cupriavidus necator, or Methylobacterium extorquens, in which acetoacetyl-CoA is furthermore an essential intermediate of the anabolic metabolism. As a proof-of-concept, introducing the MVA pathway in M.…”
Section: Metabolic Engineering Toward Industrial Productionmentioning
confidence: 99%
“…Prakash et al [26] isolated a bacterium from soil of coastal region of India and identified as Burkholderia pseudomallei using 16S rRNA gene amplification. Agrawal et al [27] reported that twenty four isolates of Pseudomomas putida isolated from soil samples and observed phenotypic characterization of these isolates. Osman et al [28] isolated Microbacterium from soil sample and carried out molecular characterization as the 16s rRNA gene Biradar et al [29] researched PHB producing Bacillus species isolated from agricultural soil and characterized using 16S r-RNA sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…• Pseudomonas. Son reconocidas como agentes de control biológico (Agrawal et al, 2015) y promotores de crecimiento vegetal (Cano, 2011). Conservan las propiedades físicas y la oxigenación del suelo, transportadas a la rizosfera por medio de los canales de irrigación subterránea que se filtran con la lluvia y entran en contacto con la raíz de la planta (Quispe Pantoja, 2014).…”
Section: Bacterias Asociativasunclassified